KARAKTERISTIK FISIK FLAKE BERBAHAN BAKU TEPUNG JAGUNG, TEPUNG AMPAS TAHU DAN MOCAF - Nur Karimah Rakhmawati; Ahmad Nafi; Andrew Setiawan Rusdianto (Berkala Ilmiah Pertanian, 2019)
ABSTRACT Flake is made from cereals such as wheat, corn, rice, or tubers. Indonesia's wheat imports in 2017 rose about 9% to11.48 million tons. One of the local food stuffs used in the manufacture of flake is corn flour. However, the protein content is still very low at around 9.2%. Then needed other materials that can increase the added value of the dregs know. The addition of mocaf containing starch is high enough to help maintain flake crispness. The purpose of this research is to know lightness, hue, water absorption, and rehydration time of corn flour flour, dregs and mocaf. This research was conducted on three stages, namely: 1) making tofu waste flour, 2) flake processing, 3) physical properties test. The design of the study used CRD (Completely Randomized Design) factorial with one factor, namely: corn flour, tofu waste flour, and mocaf (5% : 35% : 60%; 5% : 40% : 55%; 5% : 45% : 50%; 5% : 50% : 45% dan 5% : 55% : 40%) with four repetitions. The result of analysis showed that flake of corn flour, tofu waste flour and mocaf had the physical characteristic of color with lightness value of about 72,83 - 80,75; hue value of about 107.36 - 108.03 (yellow); water absorption value of about 67.27 - 117.25%; and rehydration time of about 321 - 562 seconds. Keywords: flake, mocaf, tofu waste flour, corn flour ABSTRAK Flake terbuat dari serealia seperti gandum, jagung, beras, atau umbi-umbian. Impor gandum Indonesia pada 2017 naik sekitar 9% menjadi 11,48 juta ton. Oleh sebab itu perlu inovasi dalam rangka pemberdayaan pangan lokal untuk pembuatan flake dengan menggunakan bahan tepung jagung. Namun, kandungan proteinnya masih sangat rendah yaitu sekitar 9,2%. Maka diperlukan bahan lain yang dapat meningkatkan nilai tambah yaitu ampas tahu. Penambahan mocaf yang mengandung pati cukup tinggi dapat membantu mempertahankan kerenyahan flake.Tujuan penelitian ini untuk mengetahui lightness, hue, daya serap air, dan waktu rehidrasi flake tepung jagung, tepung ampas tahu dan mocaf. Penelitian ini dilakukan dengan tiga tahap, yaitu: 1) pembuatan tepung ampas tahu, 2) pembuatan flake, 3) uji fisik. Rancangan penelitian menggunakan RAL (Rancangan Acak Lengkap) dengan perlakuan formulasi tepung jagung, tepung ampas tahu dan mocaf (5% : 35% : 60%; 5% : 40% : 55%; 5% : 45% : 50%; 5% : 50% : 45% dan 5% : 55% : 40%) dilakukan empat kali pengulangan. Hasil analisis menunjukkan bahwa flake tepung jagung, tepung ampas tahu dan mocaf memiliki karakteristik fisik lightness 72,83 – 80,75; nilai hue 107,36 –108,03 (yellow); nilai daya serap air 67,27 – 117,25%; dan waktu rehidrasi 321 – 562 detik. Kata Kunci: flake, mocaf, tepung ampas tahu, tepung jagung